Aerobic, resistance and combined training for adults with chronic kidney disease: A protocol for a systematic review and network meta-analysis. Issue 49 (4th December 2020) - Zeng, Rong; Lai, Honghao; Li, Zhuoyan; Chen, Beibei; Wang, Lu; Zhang, Yali
Abstract: Background: Chronic kidney disease (CKD) as a disease that poses a great threat to human health, which has become a public health issue of great concern. Studies have found that exercise training has a positive effect on improving the condition of chronic kidney disease. We will conduct a network meta-analysis to assess the effects of aerobic training, resistance training and combined aerobic and resistance training in treating CKD patients. Methods: We will search PubMed, EMBASE, Medline, Cochrane Central Register of Controlled Trials (CENTRAL), and Web of science to identify randomized control trails (RCTs) that assessed the effect of different exercise training for CKD patients. Cochrane Handbook will be used to evaluate the risk of bias of included articles. We will use Stata or R software to perform data analysis. Results and Conclusion: Our systematic review and network meta-analysis will be the first study that investigates the effect of different exercise training for CKD patients, and will provide evidence for management of chronic kidney disease. Ethics and dissemination: The data involved in this study are from published articles. For this reason, there is no need for ethical approval or patient consent. Trial registration: the registration number was: CRD42020157280